1298 Methionine:lysine ratio for crossbred suckling calves fed milk replacer and an amino acid complex. (1st October 2016) - Chagas, J. C.; Ferreira, M. A.; Entjes, M. R.; Machado, F. S.; Costa e Silva, L. F.; Marcondes, M. I.
Abstract: Knowledge about the amino acid (AA) requirements of dairy cattle is rare, and information regarding limiting AAs for suckling calves does not exist. Due to the difficulties in studying the AA requirements for ruminants, research is necessary to evaluate and determine optimal levels when including these AAs in the diet. Based on studies demonstrating lysine (Lys) and methionine (Met) as limiting AAs for neonates, we hypothesized that it is possible to determine the Met:Lys ratio that maximizes the performance of suckling dairy calves. This study evaluated the effect of increasing dietary Met:Lys ratios (DMLR) on performance and body composition of crossbred suckling calves of two different ages. Thirty-six male calves (Holstein-Gyr) were introduced in the experiment on the eighth day of age and randomly distributed among two slaughter ages (16 animals slaughtered at 30 d of age, and 20 animals slaughtered at 60 d of age) and four DMLR (44, 48, 52, and 56%), which were provided in the form of an AA complex (18.93 g) added to 905 g of milk replacer. The experimental diets were provided without permission of refusals, so the intake of dry matter and nutrients were the same for all animals, regardless of DMLR. Average daily gain (ADG), gain composition and body composition were evaluated separately for the two age groups for the linear and quadratic effects of DMLR. When necessary, the linear-plateau model was adjusted. Calves from 0 to 30 d of age did not show an improved performance due to increased DMLR; it is possible that animals up to 30 d of age had other metabolic priorities over body growth and protein deposition. For calves from 30 to 60 d of age, a linear-plateau response was observed for ADG and crude protein gain (CP); the greatest ADG observed was 590 g/d for a DMLR of 52.56% ( P = 0.001), and the greatest CP deposition observed was 89 g/d for a DMLR of 52.33% ( P = 0.027). Total body CP presented a quadratic behavior, with a maximum of 11.72 kg of CP for a DMLR of 53.91% ( P = 0.040). The increased DMLR did not influence performance of calves from 0 to 30 d, and the optimal DMLR that ensured the best performance of calves from 30 to 60 d of age was situated between 52 and 54%.